2022
DOI: 10.3390/ijerph19020976
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Trace Elements in Erythrocytes as Endocrine Disruptors in Obese and Nonobese Women with Polycystic Ovary Syndrome

Abstract: Introduction: Polycystic ovary syndrome (PCOS) is one of the most commonly recognized endocrinopathies in women. The literature lacks clear data that allow any meaningful conclusions to be drawn about the influence of trace elements in erythrocytes on the biochemical parameters of PCOS. Materials and methods: This study was conducted among 47 women meeting the Rotterdam criteria for the diagnosis of polycystic ovary syndrome. The research groups included women with PCOS with different BMI values (body mass ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Several studies support our findings. Pokorska-Niewiada et al showed that trace element disturbances, including nickel, can increase body mass index and contribute to endocrine disorders (33). A study from Spain found that the trace element nickel in fat is the highest, highlighting the potential role of nickel in obesity and obesity-related diseases (34).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies support our findings. Pokorska-Niewiada et al showed that trace element disturbances, including nickel, can increase body mass index and contribute to endocrine disorders (33). A study from Spain found that the trace element nickel in fat is the highest, highlighting the potential role of nickel in obesity and obesity-related diseases (34).…”
Section: Discussionmentioning
confidence: 99%
“…Pokorska-Niewiada et al [ 19 ] identified that the relationship between the level of trace elements (namely Zn, Ni, Fe, Mn, Cu, Mg) and the level of hormones suggests that, in obese women with PCOS, nickel may play a role in inhibiting the processes of folliculogenesis and ovulation. Trace elements have been proven to have a strong influence on the normal metabolism of the body through interaction with many enzymes and hormones and play an important role in the proper course of ovulation.…”
mentioning
confidence: 99%